Removable Partial Denture after Gunshot Injury: Five Year Follow-Up - Pellizzer, Eduardo Piza [UNESP]; Goiato, Marcelo Coelho [UNESP]; Almeida, Daniel Augusto De Faria; Falcon-Antenucci, Rosse Mary [UNESP]; Lemos, Cleidiel Aparecido Araujo [UNESP]; De Souza Batista, Victor Eduardo [UNESP]; Verri, Fellippo Ramos [UNESP] (Wolters Kluwer, 2017)
The aim of this study was to report a patient of rehabilitation with removable partial denture retained by implants in-patient who suffered injury after firearm shooting. A 19-year-old man presented to the hospital of the Val Paraíso city after being hit by a bullet in the right on the face, affecting the teeth 12 to 16. The surgery to remove the shards of teeth, and bullet was performed. Surgical team opted for installation of implants without bone grafts; however, due to extensive loss of alveolar bone, only 3 tilted implants (2 Ø3.75×8.5mm and 1 Ø3.75×10mm) were installed. After recovery, the patient was referred to the Araçatuba Dental School - UNESP for the rehabilitation on the affected region. The difficulty of rehabilitation with conventional fixed prostheses was verified during the prosthetic phase. This way, it was opted for rehabilitation with removable partial dentures associated with dental implant. Two attachment system ERA (ERA, Sterngold) were positioned in the bar to make the removable partial denture. After 5 years of follow-up, the authors can conclude that the use of removable partial denture retained by implants is effective for functional and aesthetic rehabilitation, favoring socialization and self-esteem of the patient.
Keywords: Dental implants; oral rehabilitation; overdenture; removable partial denture; shotgun